Correlation of Body Mass Index and Kellgren-Lawrence Degrees in Genu Osteoarthritis - Hardiyanti, Vien; Devi, Mariane; Setiawan, I Made Buddy; Wungou, Herman P. L. (Talenta Publisher, 2020)
Background: Obesity is a major risk factor for osteoarthritis. Objectives: The aim of this study is to determine the correlation between body mass index with Kellgren-Lawrence degree in genu osteoarthritis patients. Methods: This study used cross-sectional design on 97 participants diagnosed with genu osteoarthritis in Siloam Hospital Kupang in the period January-December 2017. Measurement of height and weight was carried out for the calculation of Body Mass Index. Kellgren-Lawrence degrees were obtained with x-ray photos. Results: Most patients were women (69 patients, 71.7%), 50-59 years old (34 patients, 35.1%), with obesity (61 patients, 62.9%). Conclusion: There was a significant correlation between BMI and Kellgren-Lawrence degree in genu osteoarthritis (p = 0.000). Keywords: BMI, Kellgren-Lawrence, obesity, osteoarthritis genu Latar Belakang: Obesitas merupakan faktor risiko terjadinya osteoartritis pada lutut. Tujuan: Tujuan dari penelitian ini adalah untuk menentukan korelasi indeks massa tubuh (IMT) dengan derajat Kellgren-Lawrence pada pasien penderita osteoartritis genu. Metode: Penelitian ini menggunakan metode cross-sectional yang dilakukan pada 97 responden yang didiagnosis dengan osteoartritis lutut di Rumah Sakit Siloam Kupang pada periode Januari-Desember 2017. Derajat Kellgren-Lawrence ditentukan berdasarkan foto x-ray konvensional. Hasil: Penderita osteoartritis terbanyak adalah perempuan (69 pasien, 71,7%), berusia antara 50-59 tahun (34 pasien, 35,1%), dan dengan IMT kategori obesitas (61 pasien, 62,9%). Kesimpulan: Terdapat korelasi signifikan antara IMT dan derajat Kellgren-Lawrence pada penderita osteoartritis genu. (p = 0,000). Kata kunci: IMT, Kellgren-Lawrence, obesitas, osteoartritis genu